Non-penetrating chest blows and sudden death in the young. Issue 6 (1st November 2000) - Thakore, S; Johnston, M; Rogena, E; Peng, Z; Sadler, D
Abstract : Sudden death in the young after low energy anterior chest wall impact is an under-recognised phenomenon in this country. Review of the literature yields several American references to commotio cordis, mainly in the context of sporting events. Two cases are reported of sudden death in young men as a result of blunt impact anterior chest wall trauma. It is suggested that these cases draw attention to a lethal condition of which many practitioners are unaware.